Labor Dynamics: The Influence of District Minimum Wage and Inflation on Employee Turnover in West Java’s Manufacturing Sector - Suparto, L; Kusumadewi, R Neny (Finance and Business Management Journal, 2025)
This study examines the effects of district minimum wages and inflation on actual employee turnover in the manufacturing sector of West Java, Indonesia, during the post-pandemic period of 2022–2024. Using a panel data regression approach with fixed effects, the research analyzes data from 27 regencies and cities to assess how economic variables influence labor mobility. The results show that both district minimum wage and inflation significantly affect turnover rates. While higher minimum wages are associated with lower turnover—supporting efficiency wage theory—the positive coefficient for inflation indicates that rising prices erode real income, leading to increased turnover. The simultaneous significance of both variables reflects a complex interaction: wage increases can enhance retention, but their effectiveness is undermined when inflation outpaces nominal gains. This finding aligns with dual labor market theory, suggesting that minimum wage hikes may shift manufacturing jobs closer to the conditions of primary labor markets, though inflation can reverse these gains. The study concludes that to maintain workforce stability, wage policies must consider inflation-adjusted income levels. Policy recommendations include developing inflation-sensitive wage adjustment mechanisms, offering inflation-indexed compensation packages at the firm level, and implementing worker training programs to strengthen resilience to economic shocks. These measures aim to balance wage growth with purchasing power and mitigate the destabilizing effects of labor turnover in the region’s manufacturing industry.